THE PENAMBAHAN TERAPI LATIHAN MC.KENZIE PADA INTERVENSI SHORT WAVE DIATHERMY (SWD), TRANSCUTANEUS ELECTRICAL NERVE STIMULATION (TENS) DAN MASSAGE DAPAT LEBIH MENURUNKAN NYERI PINGGANG PADA KASUS LOW BACK PAIN - Kurniasih, Endah (Majalah Ilmiah Fisioterapi Indonesia, 2013)
This research aimed to identifi addition intervention in Mc. Kenzie exercise, short wave diathermi, transcutaneous electrical nerve stimulation and massage reduce back pain in low back pain problem . Method : This research is using pre test and post test control group design. Patients were randomised into two groups : the Control Group (CG) that use SWD, TENS, and massage is 10 patients. The Experimental Group (EG) that SWD, TENS, massage and Mc.Kenzie exercise is 10 patients too. Result : The result of CG test which using compare means with paired sample t-test, p<0,05 (p=0,000) that mean the intervention in CG is having significant to reduce pain. In the result of EG test which using compare means with paired sample t-test, p<0,05 (p=0,000) that mean the intervention in EG is having significant to reduce pain. The result test researcher using compare mean test with Independent sample t-test, p<0,05 (p=0,003), that means there are significant different between EG result and CG result. In one tail hypothesis got result p<0,05, so it shows that intervention in EG more effective significantly than CG in to reduce low back pain . Conclusion : Addition intervention in Mc. Kenzie exercise, short wave diathermi, transcutaneous electrical nerve stimulation and massage reduce back pain in low back pain problem.
Keywords: low back pain, reduce pain, Mc.Kenzie exercise.